A generikus gyógyszeripar törvényi szabályozása és annak hatásai - Petőházi Zoltán (2015)
Due to the efforts to reduce spending on health insurance funds, generic medicines have grown considerably in importance all around the world. The production of innovative drugs entails R&D investment of approximately 0.5 to 1.5 billion US dollars, financed by relatively higher consumer prices set by producers in order to sustain innovation. Generic drugs are produced once the patent of original drugs have expired and have the same effect, as proven by bioequivalence study. One of the primary objectives of this paper is to examine the measures taken to maintain the equilibrium between these two segments of the pharmaceutical industry. The pharmaceutical market of the United States of America was regulated already back in 1984 by the Waxman-Hatch Act which extended the number of years the patent was valid for, and at the same time, reduced the period needed for generics to enter the market after the patent has expired – by introducing Abbreviated New Drug Application. This was an attempt to establish equilibrium in the market, the same as Europe was striving for. Several organizations came to existence within the industry aiming to harmonize legislation, like the European Patent Organization and the EMEA which started its operations in 1995. The SPC and the notion of data exclusivity were created to extend the patent period of innovative companies. The expenditures of the National Health Insurance Fund of Hungary between 1994 and 2006 in Hungary exceeded the planned annual spend every year. The National Health Insurance Fund of Hungary exceeded its annual expenditure plan between 1994 and 2006. As a result of the measures taken between 2000 and 2006 –which have proven absolutely ineffective- we could see a period of growth from the fund’s perspective. Austerity measures were gradually introduced after law XCVIII in 2006 had entered into force but the regulation of the generic market remained incomplete. The introduction of generic incentive system in pharmacies, sealed-bid auction and order drugs by International Nonproprietary Names all served the reduction of expenditures. The measures initiated by the Széll Kálmán Programme made a huge impact. This is what I would like to demonstrate through my analysis which takes a closer look at 6 drugs belonging to the same therapeutic category containing 40mg of atorvastatin, and examines their  turnover data (both on a country and on a pharmacy level), changes in their prices and issued reimbursement volumes (the sources of my data are from the OEP database and pharmacy softwares).All parameters examined by my research have demonstrated the success of the regulation described above in the given drug segment. At the same time, solely finance driven substitution may give rise to some (mainly) professional concerns – it is the duty of futurer regulations/legislations to address these issues.